Code Mixing Found in Fellexandro Ruby's Youtube Channel - Kusumayanti, Ni Putu Ria; Ardiantari, Ida Ayu Putri Gita (Universitas Negeri Padang, 2024)
This study aimed to analyze the types of code mixing and the reasons of code mixing used in Fellexandro Ruby YouTube channel. The data that were used in this study were utterances in video content entitled People in Their 20s Must Know These 5 Things: My 3.2M Views Buka Talks that taken from Fellexandro Ruby YouTube channel. This study used direct observation methods in collecting data. The steps that were done in collecting data were transcribing data, note-taking, and identifying data. Data were analyzed using theory from Muysken (2000) to analyze the types of code mixing and the theory from Hoffmann (1991) to analyze the reason of code mixing. The result of data analysis was presented descriptively by providing detailed explanations. The study showed that alternation, congruent lexicalization and insertion are the kind of code mixing that were used by Fellexandro Ruby in this channel. Insertion was the most dominant type with a total of 25 data. Meanwhile, the reason for using code mixing were expressing group identity or solidarity, talking about a particular topic, interjection, repetition used for clarification and quoting somebody else. Talking about a particular topic was common reason for code mixing that found in the data with a total of 25 data.